Value-Added Tax (VAT) Development and Reform History—A Study of VAT Evolution Around the World and in China - Tianlong, Hu (Frontiers of law in China, 2022)
Value-added Tax (VAT), a turnover tax levied on the value appreciated in commodities production, circulation and sale, has been widely practiced by economies worldwide for its neutrality. From the international perspective, European Union VAT and New Zealand VAT stand out as characteristic models of VAT development and reform history. With changing economic development models and the growth of e-commerce businesses, VAT systems have been upgraded to meet taxation challenges brought about by the digital economy. Recently, VAT policies and measures have been introduced particularly to combat the COVID-19 impact. In China, the VAT system has been reformed constantly over the past 40 years and has been converging with international practice. China now needs to address emerging VAT issues through legislation, tax incentives, and tax-rate grades so as to meet challenges in VAT collection and management and to suit the “new normal” of economic development.